2014
DOI: 10.1007/s00737-014-0474-z
|View full text |Cite
|
Sign up to set email alerts
|

Associations of anxiety disorders, depressive disorders and body weight with hypertension during pregnancy

Abstract: The purpose of this study was to prospectively examine the relationships between maternal DSM-IV-TR anxiety disorders, depressive disorders, and body mass index (BMI) with arterial hypertension and blood pressure during pregnancy. In the Maternal Anxiety in Relation to Infant Development (MARI) study, N = 306 women were enrolled in early pregnancy and repeatedly assessed during peripartum period. DSM-IV-TR anxiety and depressive disorders prior to pregnancy, lifetime anxiety/depression liability, and BMI durin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
18
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(18 citation statements)
references
References 53 publications
0
18
0
Order By: Relevance
“…Depressive symptoms were measured through the Beck Depression Inventory-II [54], Edinburgh Postnatal Depression Scale [55], and BSI-GSI [51]. iCBT interventions in this meta-analysis exerted a significant effect on improving depressive symptoms (Z=9.42, P <.001) with medium to large effect size of 0.63 (Figure 5).…”
Section: Resultsmentioning
confidence: 99%
“…Depressive symptoms were measured through the Beck Depression Inventory-II [54], Edinburgh Postnatal Depression Scale [55], and BSI-GSI [51]. iCBT interventions in this meta-analysis exerted a significant effect on improving depressive symptoms (Z=9.42, P <.001) with medium to large effect size of 0.63 (Figure 5).…”
Section: Resultsmentioning
confidence: 99%
“…Medical complications impact not only the health and well‐being of the mother but also her developing infant (and the entire family). For example, diseases such as preeclampsia and gestational diabetes have a strong association with high maternal morbidity, hospitalization, birth complications, and neonatal mortality …”
Section: Introductionmentioning
confidence: 99%
“…For example, diseases such as preeclampsia and gestational diabetes have a strong association with high maternal morbidity, hospitalization, birth complications, and neonatal mortality. 19 Aside from the physical implications, a medically complicated pregnancy can also be a source of significant stress and anxiety for mothers. [20][21][22][23] Medical complications of pregnancy can invoke stressful emotional postpartum responses in parents which differ from the usual stresses associated with parenthood.…”
Section: Introductionmentioning
confidence: 99%
“…Studies of the non-pregnant populations have shown that these mental disorders are associated with the development of hypertension [ 1-3 ]. In particular, individuals with depressive and anxiety disorders may be more prone to hypertension because of a presumed unhealthy lifestyle and associated changes in the autonomic nervous system, the hypothalamic-pituitary adrenal axis, and the immune system [ 3-5 ].…”
Section: Introductionmentioning
confidence: 99%